A qualitative Study on Algae in Abdullah Abu-Nadjem Oasis, Al-Dewanyah,Iraq - Alasady, R. K. Abed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study was conducted on spring-fed(Abdullah Abu-Nadjem Oasis)west of AlDewanyah province,Iraq. ,during Winter 2007.    The results indicate that water quality was neutral tend to be slightly alkaline pH was 7.7 and 7.4 for station(1)and station (2) respectively.   Total hardness value of water about 1520 and 1488 mg/l.for two stations respectively ,This high values of hardness may be due to Calcium ions 397.5 and 395.5mg/l.for two stations. According to Salinity values (1.58 - 2.22) â€°(ppt) ,water of oasis may be classified as brackish water, the oasis water was well aerated dissolved oxygen was 5.3 and 7.4 mg/l.     On the other hand about (58) algal taxa were recorded in this study Diatoms(Bacillariophyceae)were the dominant microalgae (58.6%),followed by blue greens(Cyanophyceae)(20.6%),While the Chlorophyceae and Charophyceae were the lower in occurrence .The dominant of Diatoms was recorded in most of Iraqi inland water bodies.,